Frontispiece: Quantum Crystallography: Current Developments and Future Perspectives. Issue 43 (1st August 2018) - Genoni, Alessandro; Bučinský, Lukas; Claiser, Nicolas; Contreras‐García, Julia; Dittrich, Birger; Dominiak, Paulina M.; Espinosa, Enrique; Gatti, Carlo; Giannozzi, Paolo; Gillet, Jean‐Michel; Jayatilaka, Dylan; Macchi, Piero; et al.
Abstract : A tale of two worlds : The painting used for the frontispiece is F. Rasma's "Mehr Licht" from 1991. We are grateful to the artist for his permission to reproduce it here. "Mehr Licht!" (more light!) can be understood as the very human outcry for more insight, more understanding, more knowledge. It is said to be Johann Wolfgang von Goethe's last words, one of the greatest German thinkers, scientists and poets. In the context of quantum crystallography, the artwork and its title represent the possibilities of this new science to generate more and deeper knowledge by using intense light in terms of radiation and by amalgamation of two mature disciplines – quantum mechanics and crystallography onpage 10881 ff.